Language learning strategies employed by higher and lower achieving students in learning speaking - Suci Rahmi Amjusfa; Burhanuddin Yasin; Kismullah Abdul Muthalib (Universitas Syiah Kuala, 2021)
The objectives of this research were to find out the types of language learning strategies employed by higher and lower achieving students on speaking skill and to find out the impacts of language learning strategies employed by them. A questionnaire was used as the instrument of this study. The sample of this research were 82 students who were chosen based on the criteria: (1) the students already passed all the Speaking I to IV classes, (2) the students consist of higher achieving students (score ≥B) and lower achieving students (score ≤C), and (3) the students allowed the researcher to obtain their speaking scores. Thus, purposive sampling was used here. In this research, the researcher used Strategy Inventory for Language Learning (SILL) by Oxford (2003) to determine the students’ language learning strategy. The result revealed that the higher achieving students used memory, cognitive, compensation, metacognitive, affective, and social strategies in learning speaking. On the other hand, the lower achieving students generally did not use the learning strategies in their learning activities. Therefore, as the impact of this learning habit, they do not possess a good speaking ability and achieve low scores in speaking class.